2021
DOI: 10.1038/s41467-021-26180-4
|View full text |Cite
|
Sign up to set email alerts
|

DHHC9-mediated GLUT1 S-palmitoylation promotes glioblastoma glycolysis and tumorigenesis

Abstract: Glucose transporter GLUT1 is a transmembrane protein responsible for the uptake of glucose into the cells of many tissues through facilitative diffusion. Plasma membrane (PM) localization is essential for glucose uptake by GLUT1. However, the mechanism underlying GLUT1 PM localization remains enigmatic. We find that GLUT1 is palmitoylated at Cys207, and S-palmitoylation is required for maintaining GLUT1 PM localization. Furthermore, we identify DHHC9 as the palmitoyl transferase responsible for this critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 30 publications
2
83
0
Order By: Relevance
“…GLUT1, as an important transmembrane protein, regulates the entry of extracellular glucose into cells and serves as a "valve" to control the constant glucose uptake by cells [33]. In previous studies, GLUT1 was reported to be increasingly expressed in many malignant tumors and correlated with poor clinical outcomes, thus GLUT1 was considered a main prognostic indicator for tumorigenesis [34][35][36]. Few studies have explored the role of GLUT1 in immunoregulation in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1, as an important transmembrane protein, regulates the entry of extracellular glucose into cells and serves as a "valve" to control the constant glucose uptake by cells [33]. In previous studies, GLUT1 was reported to be increasingly expressed in many malignant tumors and correlated with poor clinical outcomes, thus GLUT1 was considered a main prognostic indicator for tumorigenesis [34][35][36]. Few studies have explored the role of GLUT1 in immunoregulation in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, palmitoylation at the C-terminal of GSDME, a member of the cleavage of gasdermin family proteins, can enhance chemotherapeutic drug-induced pyroptosis by modulating GSDME-mediated downstream signal 95 . ZDHHC9 facilitates palmitoylation of Glucose transporter (GLUT1) at Cys207 and thus increases its plasma membrane localization, which is critical for glucose supply during glioblastoma (GBM) tumorigenesis 96 . Palmitoylation of Smad3 catalyzed by ZDHCH19 promotes the activation of the Transforming Growth Factor-beta (TGF-β) signaling pathway and its interaction with EP300, and enhances expression of mesenchymal markers in the mesenchymal subtype of GBM 97 .…”
Section: Protein Palmitoylation Regulates Other Signalingmentioning
confidence: 99%
“…The wide application of 2-flourine-18[(18)F] fluoro-2-deoxy-D-glucose (FDG) positron emission tomography–computed tomography (PET–CT) demonstrated the glycolytic phenotype in most cancers. Therefore, ROS-induced oxidation and inactivation of GAPDH and PKM2 can cause the depression of both aerobic and anaerobic glycolysis, leading to decreased proliferation and/or cell death due to shortages of energy and tricarboxylic acid cycle (TCA)-derived biosynthesis, especially in cancer cells in early stages that are more dependent on glycolysis [ 10 , 11 , 12 ]. Despite these reports linking overt ROS damage to metabolic pathways and other cellular components, it is noteworthy that cancer cells also adapt to such overwhelming ROS levels and metabolic impairment [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%